2021
DOI: 10.3390/civileng3010001
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Local and Combined (Global) Scours on Piers-on-Bank Bridges

Abstract: This paper examines the scour problems related to piers-on-bank bridges resulting from frequently flooded and/or constricted waterways. While local scour problems for bridge piers in riverine channels have been addressed extensively in the literature, there have been few studies addressing piers-on-bank scour scenarios. A comprehensive three-dimensional finite element analysis using the element removal (ER) technique has been performed on a recently constructed bridge with an observable scour problem on multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…Scouring in the part of a river where water does not normally flow, for instance, piers on the flood plain in compound channels and the bank, has also been investigated 24 , 25 . Wu et al 26 investigated scouring at square and semicircular abutments in an ice-covered channel.…”
Section: Introductionmentioning
confidence: 99%
“…Scouring in the part of a river where water does not normally flow, for instance, piers on the flood plain in compound channels and the bank, has also been investigated 24 , 25 . Wu et al 26 investigated scouring at square and semicircular abutments in an ice-covered channel.…”
Section: Introductionmentioning
confidence: 99%
“…Contrasting with piers in the river basin, the piers-on-bank experiences scour only during high-waters, and dry debris may accumulate in the scour holes until the next high-water. Figure 2 shows the envisioned mechanisms of local scour surrounding a single bridge pier, where the soil/sediment mass may be removed due to high water velocities and increased turbulence (which are functions of the hydrodynamic characteristics of the river flow), and the competence of the geomaterial surrounding the bridge pier to resist the scouring process [3]. The wet-dry cycle may present a different damaging effect to the piers and currently no studies have been identified for such a bridge.…”
Section: Introductionmentioning
confidence: 99%